KETERKAITAN ANTARA POLA ASUH DAN INNER CHILD PADA PERKEMBANGAN ANAK USIA DINI: SEBUAH TINJAUAN KONSEPTUAL [THE RELATIONSHIP BETWEEN PARENTING PATTERNS AND INNER CHILD IN EARLY CHILDHOOD'S DEVELOPMENT: A CONCEPTUAL REVIEW] - Siti Nuroh (Acta Islamica Counsenesia: Counselling Research and Applications, 2022)
The purpose of this study was to describe the relationship between parenting and the inner child in early childhood development. This study uses a literature study approach with a descriptive type of research. The results of this study are three kinds of impacts of different parenting styles on early childhood development, namely: (1) If someone knows the inner child and is bad at responding, then it is also bad in producing responses when interacting; (2) If someone knows the inner child and is good at accepting it, it will give birth to good activities or interactions and be able to develop themselves to be even better; and (3) If a person is aware of the inner child and is able to process his wounds into positive or good things, then good things will also be born.